(untitled) (Media Kesehatan Masyarakat Indonesia, 2022)
The World Health Organization (WHO) and the Indonesian government have advised the use of cloth face masks by medical and non-medical personnel to prevent Covid-19 transmission. However, many people find it difficult to wear these masks when doing various activities outside their home. The cloth face masks used in Indonesian communities vary significantly in models, materials, and number of layers with a significant number providing discomfort to people. Therefore, this research aims to identify the factors that influence the comfort of cloth face mask model circulating in the public. Phenomenological research design through completed participant observation and open-ended interview with seven lecturers and three education personnel were used to obtain more in-depth data. The results showed that despite the availability of various models in circulation, none were comfortable to use while talking and breathing. On the other hand, their straps use a lot of materials causing pain in the earlobe. Therefore, people prefer irrespective disposable masks of their ability to pollute the environment when not properly disposed. In conclusion, it is necessary to have a homemade cloth face mask that provides comfort to people.